2021
DOI: 10.1186/s13690-021-00558-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and improvement in inappropriate parental behaviors of mothers with young children: a retrospective cohort study conducted in collaboration with a local government

Abstract: Background Inappropriate parental behaviors of mothers toward young children require further study; few epidemiological studies have utilized longitudinal analysis of region-based cohorts. This study examined the frequency of incidence of and improvements in inappropriate parental behaviors of mothers with young children and related factors. Methods Among the mothers who underwent a checkup in Fukushima City in 2017, 586 mothers with data from 4-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…7 Financial support is another important element of parenting support schemes, particularly because economic deprivation underpins parenting difficulties and is a common factor in the occurrence of child abuse. 8,9 Yet, a recent study reported that the effects of expanding financial childcare support (child benefit) vary depending on household income in Japan. 10 Child benefit expansion was shown to increase parents' preference for child education in higherincome households, but not in lower-income households, indicating a need to consider ways to enhance educational preference in low-income families when providing financial support.…”
Section: Introductionmentioning
confidence: 99%
“…7 Financial support is another important element of parenting support schemes, particularly because economic deprivation underpins parenting difficulties and is a common factor in the occurrence of child abuse. 8,9 Yet, a recent study reported that the effects of expanding financial childcare support (child benefit) vary depending on household income in Japan. 10 Child benefit expansion was shown to increase parents' preference for child education in higherincome households, but not in lower-income households, indicating a need to consider ways to enhance educational preference in low-income families when providing financial support.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), child maltreatment “includes neglect, physical, sexual and emotional abuse, and fabricated or induced illness” (WHO, 2019). Since parents play the role of guardians, their socioeconomic status, psychopathology, and histories of trauma and child maltreatment are essential factors that affect child maltreatment (Arai et al., 2021; Avdibegović & Brkić, 2020; Bunting et al., 2018; Montgomery et al., 2019; Mulder et al., 2018). Child maltreatment may have a lifelong impact on the child's physical health, psychosocial outcomes, and in the long term, it is related to higher levels of poverty and unemployment (Carpi et al., 2020; Dagnino et al., 2020).…”
Section: Introductionmentioning
confidence: 99%